Carbamazepine: A Therapy for ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The efficacy of carbamazepine (CBZ) in treatment of ADHD has been determined by meta-analysis of 10 reports from the international literature reviewed at Columbia University, St Luke's-Roosevelt Hospital Center, and New York University Medical Center.